NAADP Activates two-pore channels on t cell cytolytic granules to stimulate exocytosis and killing - Davis, L; Morgan, A; Chen, J; Snead, C; Bloor-Young, D; Shenderov, E; Stanton-Humphreys, M; Conway, S; Churchill, G; Parrington, J; Cerundolo, V; Galione, A (2012)
A cytotoxic T lymphocyte (CTL) kills an infected or tumorigenic cell by Ca2+-dependent exocytosis of cytolytic granules at the immunological synapse formed between the two cells. Although inositol 1,4,5-trisphosphate (IP3)-mediated Ca2+ release from the endoplasmic reticulum activates the store-operated Ca2+-influx pathway that is necessary for exocytosis, it is not a sufficient stimulus [1-4]. Here we identify the Ca2+-mobilizing messenger nicotinic acid adenine dinucleotide phosphate (NAADP) and its recently identified molecular target, two-pore channels (TPCs) [5-7], as being important for T cell receptor signaling in CTLs. We demonstrate that cytolytic granules are not only reservoirs of cytolytic proteins but are also the acidic Ca2+ stores mobilized by NAADP via TPC channels on the granules themselves, so that TPCs migrate to the immunological synapse upon CTL activation. Moreover, NAADP activates TPCs to drive exocytosis in a way that is not mimicked by global Ca2+ signals induced by IP3 or ionomycin, suggesting that critical, local Ca 2+ nanodomains around TPCs stimulate granule exocytosis. Hence, by virtue of the NAADP/TPC pathway, cytolytic granules generate Ca2+ signals that lead to their own exocytosis and to cell killing. This study highlights a selective role for NAADP in stimulating exocytosis crucial for immune cell function and may impact on stimulus-secretion coupling in wider cellular contexts. © 2012 Elsevier Ltd.